Dynamic Harmonic Analysis of Long Term over Voltages Based on Time Varying Fourier series in Extended Harmonic Domain - Ehsan Karami; Shahram Montaser Kouhsari; Seyed Mahdi Mazhari (AUT Journal of Electrical Engineering, 2016)
Harmonics have become an important issue in modern power systems. The widespread penetration of non-linear loads to emerging power systems has turned power quality analysis into an important operation issue under both steady state and transient conditions. This paper employs an Extended Harmonic Domain (EHD) based framework for dynamic analysis of long term analysis over voltages during the transients caused by inrush currents while large power factor capacitors are located at transformer secondary side. In such cases, a combination of capacitor and inductive system impedance may lead to parallel resonance circuits of high impedance. As a significance of the developed method, it is fully frequency domain dependent solution technique which uses time dependent Fourier series, orthogonal bases and matrix operators as addressed in EHD. The proposed method has been successfully tested on several networks and the obtained results are compared to those of a time-domain software, followed by discussion on results.